Comment Élisée Reclus est devenu athée. Un nouveau document biographique - Federico Ferretti (Cybergeo, 2010)
We found in the State Archive of the Russian Federation (GARF) a handwritten notebook by one of the sisters of Élisée Reclus, which traces a short biography of her brother from his childhood to the beginning of his geographer’s career. This document does not contain a date nor a signature, so the first problem is to make the most compelling hypothesis about that. The second problem is to evaluate the relevance of this source: does it contain relevant novelties for the personal, political and scientific biography of Reclus? Finally, we propose an integral transcription of this text: we think that it is a pleasant reading.